FINANÇAS, POLÍTICA E TERRITÓRIO - INTRODUÇÃO - Christina Dias, Leila (Caderno CRH, 2009)
<!DOCTYPE html PUBLIC "-//W3C//DTD HTML 4.01 Transitional//EN"> 55todos PublicaçãoOnline do Caderno CRH: http://www.cadernocrh.ufba.br